Role of universal health coverage in improving quality of breast cancer care: an international comparison study - Yinzi Jin; Suhang Song; Zhijie Zheng; Minmin Wang (BMJ Publishing Group, 2024)
Introduction Breast cancer is the most common and lethal cancer among women worldwide. Good quality cancer care is a key pillar in improving the survival rate and reducing the burden of this cancer. This study aimed to evaluate the current status and temporal trends in global breast cancer care and to identify the association between universal health coverage and quality of breast cancer care.Methods A quality of care index for breast cancer was constructed using disease burden data from the Global Burden of Disease 2019 database. This index was evaluated and compared at global, regional and national level. The association between universal health coverage index and breast cancer quality of care index at national level was also explored.Results The quality of breast cancer care improved from 1990 to 2019, and the disparity narrowed between countries at different development levels over the same period. The universal healthcare coverage index was positively associated with national breast cancer care quality. This finding was robust across countries at low and middle levels of development, as well as more developed countries.Conclusions The identified association between universal health coverage and breast cancer care highlight the key role of developing a high-quality and resilient healthcare system for improving breast cancer care. Then expanding the universal health coverage with inclusion of breast cancer care may help improving the breast cancer care quality and reduce the disproportionate mortality due to breast cancer in low social development countries.